Influenced of Discovery Learning Model Assisted by iSpring Presenter on Students HOT Literacy Redox Reactions - Syaharani Sara; Retno Dwi Suyanti (Universitas Negeri Medan, 2024)
This research aims to determine the influence of the discovery learning model assisted by iSpring presenter media which is greater than the conventional model on students' chemistry literacy HOT abilities and aspects of developed HOTS literacy abilities. Three classes of class X pupils from SMAS Imelda Medan made up the study's population. Thirty students each from classes X MIA 2 and X MIA 3 made up the research sample. Nineteen multiple-choice questions made up the test instrument used in the study Hypothesis testing used the right-hand t test with the research results obtained by the value tcount > ttable (2.243 > 2.002) meaning that Ha was accepted and H0 was rejected, which means that the influence of using the discovery learning model assisted by iSpring presenter media on students' chemical literacy HOT abilities had a greater impact than using the conventional model. on redox reaction material with an N-Gain value of 0.75 (75.03%). Besides that, the HOT literacy skills acquired through the iSpring presenter media-assisted discovery learning paradigm were demonstrated in C5 reasoning with an 87.94% percentage in the redox reaction material.